2016
DOI: 10.2807/1560-7917.es.2016.21.16.30205
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus detection in cerebrospinal fluid from two patients with encephalopathy, Martinique, February 2016

Abstract: We report two cases of encephalopathy (one with seizures, one with electroencephalogram changes) in patients with Zika virus infection. The cases occurred on Martinique in February 2016, during the Zika virus outbreak. Awareness of the various neurological complications of Zika virus infection is needed for patients living in areas affected by Zika virus infections or for travellers to these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 5 publications
0
74
0
2
Order By: Relevance
“…After the acute viremia period, ZIKV can also be detected in the urine within two weeks as well in other fluids. 7,40 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…After the acute viremia period, ZIKV can also be detected in the urine within two weeks as well in other fluids. 7,40 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…In the specific case of ZIKV exposure, clinical/epidemiological studies have shown that both microcephalic and normocephalic babies exhibit spontaneous seizures at different intervals after birth (10,11,16,37,38). Consistent with clinical findings, ZIKV-infected mice showed spontaneous seizures beginning around 9 dpi.…”
Section: Neonatal Zikv Infection Induces Seizures In Young Mice and Imentioning
confidence: 99%
“…Yapılan bir olgu-kontrol çalışmasında, geçirilmiş ZİKV infeksiyonu öyküsünün GBS riskini 34 kattan fazla arttırdığı gösterilmiş, olgularda akut motor aksonal nöropati ile uyumlu bulgular saptanmıştır (10) . Ayrıca ZİKV infeksiyonuyla iliş-kili olarak meningoensefalit ve oküler tutuluma ait olgular bildirilmiştir (29,70) .…”
Section: Tablo 1 Semptomatik Zika Virüs Infeksiyonunda Saptanabilen unclassified